2007
DOI: 10.1007/s00428-007-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-endocrine tumours of the lung. A review of relevant pathological and molecular data

Abstract: Neuroendocrine (NE) tumours of the lung include pure and mixed forms. In the former group, a continuum of lesions is recognised ranging from benign typical carcinoids to atypical carcinoids (having a low-grade behaviour, although often associated with regional and distant metastases), to the highly aggressive poorly differentiated carcinomas of the small and large cell types. In the mixed tumour group, the NE component is extensively represented in association with any of the non-small cell carcinoma subtypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 57 publications
0
28
2
3
Order By: Relevance
“…Unsupervised classification based on the copy number alterations showed a subtype of HGNEC with a better prognosis, suggesting the existence of molecular subtypes with clinical significance in HGNEC, but this observation should be validated in a further validation set. Multiple alterations in tumor suppressors and oncogenes have been reported (Sattler and Salgia, 2003;Righi et al, 2007), however, no prognostic DEK oncoprotein in pulmonary endocrine carcinoma T Shibata et al biomarker has been currently reported in HGNEC and our study has also failed to correlate our molecular classification with known oncoproteins. Therefore we further extracted specific loci that were associated with the prognostic classification to identify a novel diagnostic biomarker.…”
Section: Molecular Classification Of Pulmonary Endocrine Tumorscontrasting
confidence: 55%
“…Unsupervised classification based on the copy number alterations showed a subtype of HGNEC with a better prognosis, suggesting the existence of molecular subtypes with clinical significance in HGNEC, but this observation should be validated in a further validation set. Multiple alterations in tumor suppressors and oncogenes have been reported (Sattler and Salgia, 2003;Righi et al, 2007), however, no prognostic DEK oncoprotein in pulmonary endocrine carcinoma T Shibata et al biomarker has been currently reported in HGNEC and our study has also failed to correlate our molecular classification with known oncoproteins. Therefore we further extracted specific loci that were associated with the prognostic classification to identify a novel diagnostic biomarker.…”
Section: Molecular Classification Of Pulmonary Endocrine Tumorscontrasting
confidence: 55%
“…According to the WHO classification of lung tumors [70] they are classified under the term "combined carcinomas". The morphology of such tumors, as well as their clinical behavior, recapitulate the specific features of the individual components, and this tumor group is described in detail elsewhere in the current issue [60].…”
Section: Meec In the Pancreas Gastrointestinal And Biliary Tractmentioning
confidence: 95%
“…I tumori neuroendocrini (NET) del polmone non sono un'unica entità, ma costituiscono uno spettro di lesioni variamente differenziate associate a caratteristiche patologiche e comportamento clinico più o meno aggressivo. I carcinoidi tipici e atipici sono le varianti meglio differenziate, mentre le forme meno differenziate sono il carcinoma neuroendocrino a grandi cellule e il microcitoma [1,2].…”
Section: Figuraunclassified